Effect of berseem supplementation to straw diets on nitrogen metabolism and nutrient utilization in cattle - Das, Asit; Singh, G P (The Indian Journal of Animal Sciences, 2012)
Adult non-castrated ruminally fistulaled cattle (4) of about 318Â±16 kg body weight were randomly distributed into 4 groups in an experiment based on 4 x 4 latin-square design to study the effect of berseem supplementation. Four dietary treatments were wheat straw ad lib. (1), supplemented with either 15% (2), 30% (3) or 45% (4) level of berseem. Straw consumption was 4.17, 4.47, 4.56 and 3.67 kg; berseem consumption was 0.00, 0.93, 1.95, 2.98 kg; total DMI was 4.17, 5.40, 6.51 and 6.65 kg/day in groups 1, 2, 3 and 4 respectively. Straw OM intake increased significantly only up to 30% level of supplementation. Digestibility of DM was 39.85, 45.61, 52.97 and 47.52% and CP was 12.12, 31.30, 45.93% and 56.5% in groups 1, 2, 3 and 4 respectively. While CP digestibility increased linearly with increased level of berseem, digestibility of other component increased significantly (P